Ultrasound as a diagnostic tool in the investigation of a pony with intestinal lymphoma. (20th August 2015) - Sherlock, C.; Dawson, L.; Mair, T.
Summary: A 21‐year‐old New Forest pony presented for evaluation of lethargy and colic. Transcutaneous abdominal ultrasonography revealed a cavitary, thick walled, mass‐like lesion that appeared continuous with the small intestine. The thick walls of the mass‐like lesion were of heterogeneous echogenicity with hyperechoic foci extending from the hyperechoic luminal surface to within the wall and there was loss of normal wall layering. These findings were confirmed grossly at exploratory celiotomy and histopathological examination of affected tissues confirmed lymphoma. The ultrasound findings facilitated a preoperative presumptive diagnosis that allowed informed decision‐making and aided case management.